Theather Association of The Religious Groups in Yogyakarta During 1960s - Rachman, Taufiq Nur (SHAHIH: Journal of Islamicate Multidisciplinary, 2019)
This research focuses on the dynamics of theaters based on religious groups (Teater Muslim, Starka, Teater KristenTeater Kristen and Sthemka) in Yogyakarta, which initially adopted realist theater and then turned into an experimental theater, from the 1950s to the 1960s. The 1950s was a time when realism exploded in Indonesian theater. Whereas the 1960s was a period when theater groups began to adapt new forms and were called the experimental theater period. For this reason, this research takes place in the 1950s to 1960s. To cover the idea of writing, research uses the theory of dramaturgy from Erving Goffman which has the view that interaction between humans is like a play of drama determined by space, time, and audience. Based on this view the theater is oriented towards religious groups understood to contest each other to present (presentations) themselves) in the fields of ideology, experimental works, and market changes.